Galatia 6:1-10 Sebagai Landasan Orang Percaya Dalam Menjalankan Tanggung Jawab Hidup di Dalam Kristus Bagi Sesama - Hermawan, Yoan Jessica; Sutrisno, Gideon (Jurnal Teologi Cultivation, 2025)
In this journal the author discusses "Studying Galatians 6:1-10 as the Foundation of Believers in Carrying Out Life Responsibilities in Christ for Others." The responsibility referred to in this journal is a trust given by God to every believer who lives in Christ for fellow human beings. The responsibility given by God is a task that must be carried out by every believer both in the church and in everyday life. One of the keys to the success of people who live in Christ is to carry out the responsibilities entrusted by God in their lives. The problem in this journal is what kind of responsibility is contained in Galatians 6:1-10 and how believers can apply the responsibility given by God based on Galatians 6:1-10. The research method conducted by the author is a method that focuses on one research method, namely the study of literature. The point is that the author will collect data by examining books, journal articles, and literature that discusses what will be written in this scientific paper. From the results of the research conducted by the author, it can be concluded that every believer who has gained trust in the responsibility of living in Christ must carry out his responsibilities to himself and to all people, especially to friends in faith. Thus, every believer correctly understands the responsibility of living in Christ according to Galatians 6:1-10.